A Reagentless Electrochemical DNA Sensor Based on a Self‐powered DNA Machine. Issue 4 (30th September 2022) - Huang, Ting; Zhang, Wenxing; Wie, Guobing; Hong, Nian; Wang, Mei; Fan, Qiqi; Yu, Qiangqiang; Liao, Fusheng; Fan, Hao
Abstract: Herein, a reagentless electrochemical DNA sensor based on a self‐powered DNA machine for detecting survivin mRNA in cells is developed. The metal‐organic framework (MOFs) loaded with DNAzyme cofactors (Mn 2+ ) is coated on PTFE rods on the Au surface and assembled with the DNA walker, overcoming the complexity of adding metal ions from the external environment. In addition, the orbital chain is modified by a synthetic bisferrocene signal marker, which further enables signal amplification. Under optimal conditions, the sensor exhibits a range from 1×10 −14 mol/L to 1×10 −8 mol/L with a detection limit (S/N=3) of 1.28 fM. Abstract : A reagent‐free electrochemical DNA sensor based on a self‐powered DNA machine was developed for the detection of survivin mRNA in cells. The metal‐organic framework (MOFs) loaded with DNAzyme cofactors (Mn 2+ ) is coated on PTFE rods on the Au surface and assembled with the DNA walker, overcoming the complexity of adding metal ions from the external environment, and to improve the sensitivity of the sensor, bisferrocene was synthesized to achieve a detection limit of 1.28 fM.